PARTISIPASI MASYARAKAT DALAM PERBAIKAN LINGKUNGAN HIDUP DI KECAMATAN TARUMAJAYA, BEKASI (Studi Korelasional antara Intensi, Konsep Diri dan Stratifikasi Sosial dengan Partisipasi Masyarakat) - Karmadi, Dadi (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2017)
and social stratification with community participation for improving the commmunity living environment, the data collected from 8 villages within Kecamatan Tarumajaya of Bekasi District and analysis conducted with regression and correlation analysis. The findings show up significant correlation between Intention (knowledge, belief, attitude, moral, and motive), self concept (social Identity, self esteem,) and Social stratification (social structure and sense of community) with community participation level the three components separately or all together forming community participation. Rapid development at Kecamatan Tarumajaya influence of social changing directly modifying of social stratification, self concept and Intention and by the end will changing of community participation level. as show up by the data collected. The policy and decision of environment Improvement program usually decided and driven from local government and the community only following up to implement without fully awareness, concern and social responsibility because they are still struggle to fulfill the basic need and improving quality of life.